Injectable remodeling hydrogels derived from alendronate-tethered alginate calcium complex for enhanced osteogenesis. (1st March 2023) - Kim, Han-Sem; Jang, JunHwee; Oh, Jun-Sung; Lee, Eun-Jung; Han, Cheol-Min; Shin, Ueon Sang
Abstract: A combination of hydrogel materials, and therapeutic agents have been actively reported to facilitate bone defect healing. However, conventionally hydrogels using cross-linker would result in low stability of the hydrogel itself, loss of agents during cross-linking, and complexity of use. In this study, alendronate was tethered to an AlA to improve its bone healing and drug-loading stability. AlA was further functionalized with Ca 2+ (AlACa). A mixture of AlACa and alginate formed AlAA hydrogel. The gelation time of AlAA was sufficient for injecting into the defect site. The hydrogel stiffness was controlled, while the stress-relaxation time was fixed. In vitro cell tests demonstrated that the AlAA promoted proliferation and differentiation behaviors. In particular, AlAA showed the best mechanical stiffness with appropriate stress-relaxation and cellular behavior, indicating that it would be beneficial as a scaffold in the bone tissue engineering field. Graphical abstract: Unlabelled Image